"Pre-metastatic niches" in breast cancer: are they created by or prior to the tumour onset? "Flammer Syndrome" relevance to address the question - Bubnov, Rostyslav; Polivka, Jiri; Žúbor, Pavol; Konieczka, Katarzyna; Golubnitschaja, Olga (The EPMA journal, 2017)
Breast cancer (BC) epidemic in the twenty-first century is characterised by around half a million deaths and 1.7 million new cases registered annually worldwide. Metastatic disease is the major cause of death in BC patient cohorts. Current statistics are much alarming from the viewpoint of the early mortality amongst BC patients with de novo metastatic disease. A new paradigm of so-called "pre-metastatic niches" may sufficiently promote our knowledge regarding potential pathomechanisms, individual predisposition and prognosis in development and progression of the metastatic disease. However, the crucial question remains unaddressed, whether hypoxic pre-metastatic niches in BC are created by or prior to the tumour onset. So far, the current interpretation of the "Seed and Soil" theory of metastasis proposing that the pre-metastatic niches are formed by primary tumours which "induce and guide" the process is incomplete, since it does not provide satisfactory explanations towards several facts overviewed in the article. The overall results of this study clearly support the working hypothesis presented by the authors proposing that the epi/genetic predisposition of individuals at risk to form the systemic hypoxic pre-metastatic niches can be established a long time before breast malignancy is clinically manifested. "Flammer Syndrome" (FS) phenotype may strongly contribute to particularly poor outcomes of metastatic breast cancer. Significance and relevance of individual FS symptoms for breast cancer metastatic disease are discussed in extenso.